Peculiarities of deformation of CoCrFeMnNi at cryogenic temperatures. Issue 19 (14th October 2018) - Tirunilai, Aditya Srinivasan; Sas, Jan; Weiss, Klaus-Peter; Chen, Hans; Szabó, Dorothée Vinga; Schlabach, Sabine; Haas, Sebastian; Geissler, David; Freudenberger, Jens; Heilmaier, Martin; Kauffmann, Alexander
Abstract: Abstract : This contribution presents a comprehensive analysis of the low temperature deformation behavior of CoCrFeMnNi on the basis of quasistatic tensile tests at temperatures ranging from room temperature down to 4.2 K. Different deformation phenomena occur in the high-entropy alloy in this temperature range. These include (i) serrated plastic flow at certain cryogenic temperatures (4.2 K/8 K), (ii) deformation twinning (4.2 K/8 and 77 K), and (iii) dislocation slip (active from 4.2 K up to room temperature). The importance of deformation twinning for a stable work-hardening rate over an extended stress range as well as strain range has been addressed through the use of comprehensive orientation imaging microscopy studies. The proposed appearance of ε-martensite as well as a previously uninvestigated route of analysis, essentially a quantitative time-dependent, strain-dependent, and stress-dependent evaluation of the serrated plastic flow in CoCrFeMnNi is provided.